2001
DOI: 10.1046/j.1526-100x.2001.009002201.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Wetlands from Abandoned Rice Fields for Nutrient Removal, and Biological Community and Landscape Diversity

Abstract: A number of experimental freshwater wetlands (150 m long × 75 m wide) with different ages since they were abandoned as rice fields, were used to analyze the prospects of multipurpose wetland restoration for such degraded areas. Nitrogen and phosphorus removal rate of the wetlands were determined monthly during the flooding season to estimate their efficiency as filters to remove nutrients from agricultural sewage. The number of wetland birds was recorded regularly to identify their habitat preferences. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 15 publications
4
33
0
3
Order By: Relevance
“…Results showed that soil quality improved with time due to accumulation of TOC, TN, TP, and improvement of soil texture. Similar results were reported in terrestrial ecosystems (Browman et al, 1990;Peng, 1995;Kosmas et al, 2000;Comin et al, 2001;Singh et al, 2001;Lee et al, 2002;Bruland & Richardson, 2004, 2005. Soil pH in riparian areas ranged from 4.90 to 5.28 in the 0-20 cm layer and 5.68 to 5.92 in the 20-40 cm layer in Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results showed that soil quality improved with time due to accumulation of TOC, TN, TP, and improvement of soil texture. Similar results were reported in terrestrial ecosystems (Browman et al, 1990;Peng, 1995;Kosmas et al, 2000;Comin et al, 2001;Singh et al, 2001;Lee et al, 2002;Bruland & Richardson, 2004, 2005. Soil pH in riparian areas ranged from 4.90 to 5.28 in the 0-20 cm layer and 5.68 to 5.92 in the 20-40 cm layer in Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Changes in the similarity index and aboveground biomass indicated an increasing trend during restoration. Comparison of vegetation changes and related indices between restored wetlands showed a general trend towards a mature community or ecosystem, which has also been observed in terrestrial systems (Peng, 1995;Comin et al, 2001). In this study, we observed that groundwater table fluctuation might limit riparian wetland ecosystem succession.…”
Section: Discussionsupporting
confidence: 78%
“…The management and conservation of specific weed communities and specialist plants have been studied (Yamada et al 2007(Yamada et al , 2013. If abandoned fields remained wet, they usually developed into wet grasslands (Comín et al 2001) or wet woodlands dominated by Salix and Alnus species (Lee et al 2002). Yamada et al (2002) reported that the number of plant species in the soil seed bank was greatest in the first year of abandonment, but it declined steadily with the process of succession in abandoned rice paddies in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Juncus effusus has been well studied with respect to its autecology (Richards and Clapham 1941a, 1941b, Lazenby 1955a, 1955b, Grime et al 1990, Ervin and Wetzel 1997, Wetzel and Howe 1999, potential interactions with other wetland plant species Wetzel 2000, 2001), and the distribution of plants occurring during succession (Comin et al 2001, Lee et al 2002, Koo 2003. Numerous studies have indicated that J. effusus is a prominent component of soil seed banks (Chippindale and Milton 1934, Champness and Morris 1948, Thompson and Grime 1979, Grime et al 1990).…”
Section: Water Analysesmentioning
confidence: 99%